The first Russian register of patients with chronic heart failure and atrial fibrillation (RIF-CHF): study design - S. N. Tereshchenko; I. V. Zhirov; N. V. Romanova; Yu. F. Osmolovskaya; S. P. Golitsyn (Рациональная фармакотерапия в кардиологии)
Chronic heart failure (CHF) and atrial fibrillation (AF) can rightly be called the epidemic of the XXI century, which are associated with high morbidity and mortality of patients. Common risk factors and pathophysiological mechanisms explain the frequent combination of CHF and AF. So far, a number of issues related to management of these patients, remains unresolved. Data on compliance with clinical guidelines and the prevalence of long-term anticoagulant therapy in this group of patients in our country is limited. The first Russian register of CHF and AF (RIF-CHF) is initiated in order to better address this problem. The results allow to develop the most rational therapeutic and diagnostic strategies and, ultimately, to improve the clinical outcomes of such severe patients.